Organizing Community Participation in Themadiredolake Agrotourism Management Institutionin Empowerment (Case Study of Madiredo Village, Pujon District, Malang Regency) - Nabila, Firyal Fauziah Iffa; Zulkarnain, Zulkarnain; Purnamasari, Ica (Universitas Negeri Malang, 2024)
Community organizing is a process or effort to form, manage, and organize communities or groups to achieve common goals and solve problems that exist in a particular social environment. The purpose of this research is to: 1) Knowing the role of community leaders and community institutions through the process of organizing community management of Telaga Madiredo Agrotourism2) Knowing the form of community participation in organizing the community management of Telaga Madiredo Agrotourism. This research uses qualitative research with a case study approach, this research uses data collection techniques, through interviews, observations, and document studies. The data was analyzed narratively using the Miles, Huberman & Saldana approach with the stages of data collection, data condensation, data presentation and conclusion drawing. To get accurate data, this research uses source triangulation and technique triangulation.The results of this study include 1) The role of community leaders and community institutions in organizing the community management of Telaga Madiredo Agrotourism is carried out through community awareness, Village Deliberation(Musdes) and the formation of the Telaga Madiredo Agrotourism management group. 2) The formof community participation in the organization of community management of Madiredo Lake Agrotourism is participating in planning, the community provides suggestions and opinions related tothe management of Madiredo Lake Agrotourism through Musdes and evaluation activities. Inimplementation, the community participates in contributions in the form of labor, funds, and promotion. Participation in the form of labor is that the community is involved in the construction of Telaga Madiredo Agrotourism infrastructure, participation in the form of community funds as investors andparticipation in the form of community promotion in promoting Telaga Madiredo Agrotourismon their personal social media. The form of community participation in utilizing the results is that the community participates as employees, the farming community cooperates with the manager of Telaga Madiredo Agrotourism, and the people who live around Telaga Madiredo Agrotourism sell drinks andsnacks. Keywords : community organizing, participation, role, community institution community